RESEARCH ON SECURE VIRUS TROJAN IN CYBERSECURITY PLATFORM - Ahmad Fajar Sidiq; Rusydi Umar; Anton Yudhana (Fakultas Ilmu Komputer dan Desain - Unsurya, 2018)
Security is main issue of this generation of computing because many types of attacks are increasing day by day. Establishing a network is not a big issue for network administrators but protecting the entire network is a big issue. There are various methods and tools are available today for destroying the existing network. In this paper we mainly emphasize on the network security also we present some major issues that can affect our network, Trojan horse virus can give rise to the leakage of internal data.Â Keywords:Security, Trojan Horse, System, Network.